IMPLEMENTASI PERATURAN BUPATI BOYOLALI NOMOR 16 TAHUN 2015 TENTANG PEDOMAN DAN TATA CARA PENGADAAN BARANG DAN JASA DI DESA (Studi Pengadaan Barang dan Jasa di Desa Kebonan Kecamatan Karanggede Kabupaten Boyolali Tahun Anggaran 2015) - Sri Riris Sugiyarti, Yassir Jatmika, Suwardi & (Transformasi, 2016)
Procurement of goods / services in the village Kebonan Karanggede Boyolali District of fiscalyear 2015 field development for the village road paving activities already carried out startingfrom the stages of preparation, implementation, monitoring, delivery, reporting andaccountability. Implementation of the decree Boyolali No. 16 of 2015 on Guidelines andProcedures for Procurement of Goods and Services In the village have been implemented, butthere are still some problems, namely: Apratur Village Government Kebonan yet to master orunderstand the contents of the decree Boyolali, as well as the low level of participation of ruralcommunities and the business world of the limited impact of socialization of Boyolali DistrictGovernment.Key Word: : Policy Implementation Procurement of Goods / Services